NMR solution structure of a DNA dodecamer containing single G.T mismatches. - Allawi, H T (1998)
The three-dimensional solution structure of the self-complementary DNA dodecamer (CGT_GACGT_TACG above GCAT_TGCAG_TGC] which contains the thermodynamically destabilizing [TG_A above AT_T] motif was determined using two-dimensional NMR spectroscopy and simulated annealing protocols. Relaxation matrix analysis methods were used to yield accurate NOE derived distance restraints. Scalar coupling constants for the sugar protons were determined by quantitative simulations of DQF-COSY cross-peaks and used to determine sugar pucker populations. Twenty refined structures starting from random geometries converged to an average pairwise root mean square deviation of 0.49 A. Back calculated NOEs give Rc and Rx factors of 0.38 and 0.088, respectively. The final structure shows that each of the single G@T mismatches form a wobble pair with two hydrogen bonds where the guanine projects into the minor groove and the thymine projects into the major groove. The incorporation of the destabilizing [TG_A above AT_T] motif has little effect on the backbone torsion angles and helical parameters compared to standard B-form duplexes, which may explain why G.T mismatches are among the most commonly observed in DNA. The structure shows that perturbations caused by a G.T mismatch extend only to its neighboring Watson-Crick base pair, thus providing a structural basis for the applicability of the nearest-neighbor model to the thermodynamics of internal G.T mismatches.